Systematic optimization of sol?gel processed Al-doped ZnO for cost-effective transparent conductive oxide - Arzaee N.A.; Za?abar F.I.; Bahrudin M.S.; Arsad A.Z.; Azman N.I.; Abd Rahman M.N.; Wan Abdullah W.S.; Chau C.F.; Mahmood Zuhdi A.W. (Springer, 2025)
Solution-based fabrication method has gained increasing attention as an alternative low-cost approach for developing transparent conducting oxide (TCO). Systematic optimization of the deposition process can greatly facilitate the formation of thin film with well-balanced optical and electrical properties. In this work, Al-doped ZnO (AZO) layer is grown by sol?gel spin-coating and various fabrication parameters are finely tuned. It is discovered that 2-methoxyethanol is the preferable solvent that produces less morphological defect in the formed AZO film. By using dynamic spin-coating, wrinkle structure is formed, which may be beneficial for reducing light loss. Further control of film thickness by changing the respective spin speed and number of layers to 3000 rpm and 3 layers enables the transparency to reach over 90% and the resistivity to be 3.22 ? 103 cm. The practicability of the optimized AZO has been demonstrated in the CIGS solar cells as front contact, suggesting that the solution-based route is a potential alternative for developing low-cost TCO. Graphical Abstract: (Figure presented.) ? The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.